Opportunities for Food waste Behavior at the Household Level in the Special Region of Yogyakarta - Herdiana Anggrasari; Dhika Cahyasita; Muhamad Ridwan (Universitas Medan Area, 2023)
Food waste has become a serious concern due to the environmental damage and financial losses it causes. Leftover food at the consumption stage is a direct consequence of consumer buying behavior. Most of the food waste occurs at the household level. This makes analysis of the causes of food waste behavior at the household level an opportunity to prevent food waste problems. The aim of the study to determine the behavior of food waste at the household level in the Special Region of Yogyakarta. Data of 203 respondents were obtained from online and offline surveys and analyzed descriptively. The findings show that households have a very positive attitude (84.66%) to avoid food waste supported by a good level of knowledge (75.88%) and a level of food management skills which is included in the high category (74.66%). The level of household eating and shopping habits that support food waste is in the medium category (51.69%). These findings have practical implications for efforts to reduce household waste by increasing positive evaluation and skills in food management